Study on the utilization of village funds to support food security in Glagah Lamongan District, East Java - Eko Sutrisno; Duwi Siswanto; Anita Rahmawati; Eksa Rusdiyana; Jenny Yudha Utama (Goodwood Publishing, 2025)
Purpose: This study is related to the use of village funds for the fiscal year 2022 to support food security at the village level and the form of activities. Research methodology: The research was conducted in four villages in the Glagah Lamongan District. Survey and questionnaire methods were used, and the data were analyzed quantitatively and depicted in the form of tables and diagrams. Results: All villages budgeted for activities related to food security because of the 20% rule of the village government. The activities carried out by the village government related to food security are both physical and non-physical. Conclusion: The findings confirm that village fund allocation policies, particularly the 20% rule for food security, have been implemented at the grassroots level through diverse activities. These efforts reflect the autonomy and initiative of local governments in addressing food-related challenges in the region. However, further support and guidance from relevant agencies are required to ensure program sustainability and effectiveness across regions. Limitations: This study was conducted in four villages in the Glagah sub-district, and the form of activity was performed in 2022. Contribution: This study provides data on village-level activities that support food security. This highlights the need for the Ministry of Village Affairs to emphasize food security goals, considering each village’s unique capacity. It also highlights the role of the DPMD and Lamongan Fisheries Office in leveraging local fisheries potential.